Dividend Policy Decisions in India: Standalone Versus Business Group-Affiliated Firms. Issue 1 (February 2019) - Labhane, Nishant B.
This study examines the determinants of two important dividend policy decisions specifically the dividend payment decision and the dividend payout level decision of 781 sample Indian firms enlisted on National Stock Exchange (NSE) over the period, 1995–2015, comparing the business group-affiliated firms with the standalone firms. In term of characteristics, the business group-affiliated firms are larger, more profitable and more levered than the standalone firms. The empirical results suggest that the dividend policy decisions of business group-affiliated firms differ significantly from that of the standalone firms. In the case of standalone firms, the firms with high investment opportunities, high financial leverage and high business risk are less likely to pay dividends, and their dividend payout levels are lower. On the other hand, the firms affiliated with business groups are more likely to pay dividends, and their dividend payout levels are higher even when they have high investment opportunities, high financial leverage and high business risk. Overall, the findings suggest that although the business groups are able to create internal capital markets (ICMs) and shield their member firms from market imperfections, they may suffer from other information asymmetry problems.